Soil-Improving Cropping Systems for Sustainable and Profitable Farming in Europe - Hessel, Rudi; Wyseure, Guido; Panagea, Ioanna S.; Alaoui, Abdallah; Reed, Mark S.; van Delden, Hedwig; Muro, Melanie; Mills, Jane; Oenema, Oene; Areal, Francisco; van den Elsen, Erik; Verzandvoort, Simone; et al. (Land (Basel), 2022)
Soils form the basis for agricultural production and other ecosystem services, and soil management should aim at improving their quality and resilience. Within the SoilCare project, the concept of soil-improving cropping systems (SICS) was developed as a holistic approach to facilitate the adoption of soil management that is sustainable and profitable. SICS selected with stakeholders were monitored and evaluated for environmental, sociocultural, and economic effects to determine profitability and sustainability. Monitoring results were upscaled to European level using modelling and Europe-wide data, and a mapping tool was developed to assist in selection of appropriate SICS across Europe. Furthermore, biophysical, sociocultural, economic, and policy reasons for (non)adoption were studied. Results at the plot/farm scale showed a small positive impact of SICS on environment and soil, no effect on sustainability, and small negative impacts on economic and sociocultural dimensions. Modelling showed that different SICS had different impacts across Europe—indicating the importance of understanding local dynamics in Europe-wide assessments. Work on adoption of SICS confirmed the role economic considerations play in the uptake of SICS, but also highlighted social factors such as trust. The project’s results underlined the need for policies that support and enable a transition to more sustainable agricultural practices in a coherent way.